42.NUTRITIONAL STATUS OF CHILDREN FROM 24 TO 59 MONTHS IN SOME PRESCHOOLS AT BAC KAN PROVINCE (Vietnam Journal of Community Medicine, 2024)
Objective: Assess the nutritional status of children 24-59 months studying at preschools located indisadvantaged districts of Bac Kan province.Subject and method: Cross-sectional descriptive study with 1034 children aged 24-59 months inBach Thong district and Cho Moi district, Bac Kan province.Results & Conclusion: The rate of underweight malnutrition in 24-59- month- old children inpreschool at Bac Kan province is 20.8%; The rate of stunting is 26.8%, the rate of wasting is 3.5%,and the rate of overweight & obesity are 3.5% and 2%, respectively. The rate of underweightmalnutrition is highest in the age group of 48-59 months, while the rate of stunting is highest in theage group 24-36 months. Most children have moderate stunting and moderate wasting. Forunderweight, most children have severe underweight.
Keywords: Child, children, malnutrition, preschool, 24-59 months old.